6 x 5 + 5 x 3 + x 2 + 4 x − 1 = a ( x − 1 ) 5 + b ( x − 1 ) 4 + c ( x − 1 ) 3 + d ( x − 1 ) 2 + e ( x − 1 ) + f
The equation above is an identity for constants a , b , c , d , e , f .
What is the value of a + 2 b + 3 c + 4 d + 5 e + 6 f ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Comparing coefficients of x^5, and x^4,resp, we get a=6, 6(5)(-1) + b =0, b=30 6(x – 1)^5 + 30(x – 1)^4 +c(x – 1)^3 +d(x – 1)^2 +e(x – 1) +f = 6x^5 + 5x^3 +x^2 +4x – 1 Comparing coefficients of x^3, we get : 6(10) – 30(4) – c = 5, c=65. Comparing coefficients of x^2, we get : 6(-10) + 30(6) – (65)(3) – d = 1, c=76. Putting x= 1, then f = 15. Putting x= 0, then -6+30-65+76-e+15=-1. e=51 So a+2b+3c+4d+5e+6f = 910
Problem Loading...
Note Loading...
Set Loading...